2022
DOI: 10.3390/md20020086
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antioxidant Activities of N-2-Hydroxypropyltrimethyl Ammonium Chitosan Derivatives Bearing Amino Acid Schiff Bases

Abstract: N-2-hydroxypropyltrimethyl ammonium chloride chitosan (HACC), a cationic quaternary ammonium salt polymer exhibiting good solubility in water, is widely used because of its low toxicity and good biocompatibility. Herein, through ion exchange reaction, we prepared N-2-hydroxypropyltrimethyl ammonium chitosan derivatives bearing amino acid Schiff bases with good biological activities. The accuracy of the structures was verified by FT-IR and 1H NMR. The antibacterial activity, antifungal activity, and scavenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Vanillin was reported to keep the activity of defense-related enzymes constant, including POD, PPO, and phenylalanine ammonia-lyase (PAL) in tomato fruit [ 18 ], it protected the grapes from postharvest rot caused by yeast, mold, and Botrytis cinerea , and extended the post-storage quality [ 19 , 20 ]. On the other hand, an amino acid derived Schiff base attracted more attention due to its special biological activities including antioxidant, and antibacterial [ 21 , 22 , 23 ]. Taurine is a naturally occurring amino acid that is widely distributed in human tissues and organs and was used as a supplementation or additive in food.…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin was reported to keep the activity of defense-related enzymes constant, including POD, PPO, and phenylalanine ammonia-lyase (PAL) in tomato fruit [ 18 ], it protected the grapes from postharvest rot caused by yeast, mold, and Botrytis cinerea , and extended the post-storage quality [ 19 , 20 ]. On the other hand, an amino acid derived Schiff base attracted more attention due to its special biological activities including antioxidant, and antibacterial [ 21 , 22 , 23 ]. Taurine is a naturally occurring amino acid that is widely distributed in human tissues and organs and was used as a supplementation or additive in food.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan and its modifications have a myriad of technology relevant properties, including antimicrobial, [32,[41][42] antifungal, [2,5,43] wound healing, [7,44] antioxidant, [41,45] materials chelator [10,27,38] and more. In the next paragraphs, we will present various modification-dependent chitosan applications.…”
Section: Features and Applicationsmentioning
confidence: 99%
“…cubense reaches 100 % at 0.5 mg mL À 1 concentration (Scheme 11). [41] Hefni et al showed that increasing the number of chitosan's amino groups using l-Ala esterification on C6À OH leads to an increase in adsorption efficiency. The uptake efficacy of three heavy metals (Mn 2 + , Pb 2 + , Al 3 + ) and total organic carbon (TOC) from wastewater was studied at different concentrations, temperatures, and contact times.…”
Section: Amino Acid Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan, with amino acid modification, is biocompatible for wound healing and tissue generation [ 8 , 9 ]. Chitosan can also be modified for antibacterial and antifungal properties to inhibit the growth of E. coli and B. cinerea [ 10 ]. Chitosan-based sprays and aerogels provide a significant reduction in bacterial growth and are good for food packaging [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%